(untitled) - Schildt, Herbert (New York, 2003)
Best-selling genius Herb Schildt covers everything from keywords, syntax, and libraries, to advanced features such as overloading, inheritance, virtual functions, namespaces, templates, and RTTI'plus, a complete description of the Standard Template Library (STL).
Keywords: C++ (Computer program language),C++ (Ngôn ngữ lập trình máy tính)